Christina Souyoudzoglou-Haywood and Christina Papoulia (eds) Archaeology of the Ionian Sea. - Dickinson, Oliver (Journal of Greek Archaeology, 2025)
The Ionian Sea is a somewhat nebulous concept, difficult to divide from the Adriatic on the north and uncertain in its extent to the south; the group of islands usually called Ionian is certainly at its centre, but for a long time the name was extended to incorporate not only Kerkyra (modern Corfu) well to the north of these but Kythera off the south-eastern peninsula of the Peloponnese. The administrative arrangements have now been changed to exclude Kythera, but Corfu remains part of the group and is the home of the Ionian University. However, it is rarely mentioned in this volume, which focusses much more on the central group of islands, particularly Kefalonia, Ithaka and Zakynthos, and is almost entirely concerned with their prehistoric archaeology. These islands have attracted attention since the beginning of Greek prehistoric archaeology, with a marked focus on attempts to identify the home of the legendary Odysseus, clearly set on an island called Ithake in the Odyssey and associated with the island called Ithaka in Classical times and now again having that name (after a long period as Thiaki). But this island has proved less productive of prehistoric remains than the much larger Kefalonia and Zakynthos, and the search for links to famous legends has tended to obscure the islands’ real significance as likely staging points on the natural sea-routes from western Greece up the Adriatic and across it to southern Italy and the central Mediterranean.